Atypical Chronic Inflammatory Demyelinating Polyneuropathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at the Royal Children's Hospital and Melbourne University, Victoria, Australia report a 12-year-old boy with a 12-month history of progressive weakness affecting extremities and neck flexion but no facial weakness.